2007
DOI: 10.1016/j.jacc.2007.01.098
|View full text |Cite
|
Sign up to set email alerts
|

Racial/Ethnic Differences in the Risk of Intracranial Hemorrhage Among Patients With Atrial Fibrillation

Abstract: Nonwhites with AF were at greater risk for warfarin-related ICH. Blacks, Hispanics, and Asians were at successively greater ICH risk than whites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
434
7
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 584 publications
(460 citation statements)
references
References 42 publications
17
434
7
2
Order By: Relevance
“…65 Differences in the propensity for bleeding between East Asian and white populations have also been described. [10][11][12] In an analysis of individuals from the USA with atrial fibrillation, Asian patients were at greater risk of w arfarinassociated intracranial haemor rhage than white individuals, despite similar inter national normalized ratios between the two groups. 11 In contrast to the risk of ischaemic events after PCI, the risk of serious bleeding in East Asian individuals seems to be greater than in white individuals.…”
Section: Consensus Statementsmentioning
confidence: 99%
See 2 more Smart Citations
“…65 Differences in the propensity for bleeding between East Asian and white populations have also been described. [10][11][12] In an analysis of individuals from the USA with atrial fibrillation, Asian patients were at greater risk of w arfarinassociated intracranial haemor rhage than white individuals, despite similar inter national normalized ratios between the two groups. 11 In contrast to the risk of ischaemic events after PCI, the risk of serious bleeding in East Asian individuals seems to be greater than in white individuals.…”
Section: Consensus Statementsmentioning
confidence: 99%
“…[10][11][12] In an analysis of individuals from the USA with atrial fibrillation, Asian patients were at greater risk of w arfarinassociated intracranial haemor rhage than white individuals, despite similar inter national normalized ratios between the two groups. 11 In contrast to the risk of ischaemic events after PCI, the risk of serious bleeding in East Asian individuals seems to be greater than in white individuals. In a study of Japanese patients undergoing elective implantation of a drug-eluting stent and treated with aspirin plus a thienopyridine (200 mg daily of ticlopidine or 75 mg daily of clopidogrel), a notable 6.5% incidence of major bleeding was observed during the 16 months of DAPT.…”
Section: Consensus Statementsmentioning
confidence: 99%
See 1 more Smart Citation
“…The safety profiles showed that all NOACs caused a lower risk of intracranial hemorrhage, but an increased risk of gastrointestinal bleeding with rivaroxaban, edoxaban, and dabigatran (150 mg twice daily) compared with warfarin. Of particular note, Asians may receive greater benefit from NOACs compared with non‐Asians, as they carry a higher risk of intracranial hemorrhage and have a greater difficulty maintaining the therapeutic range of international normalized ratio of 2 to 3 when taking warfarin 6, 7. The subgroup analyses from 4 pivotal NOAC trials indicated that NOACs may be more effective and safer in Asians than in non‐Asians 8, 9.…”
Section: Introductionmentioning
confidence: 99%
“…The risk of ICH with anticoagulation may also depend on an individual's race. Asians have a 6 times higher risk on warfarin compared to whites and are twice as likely to have an ICH when compared to blacks and Hispanics [15].…”
Section: Ich Geneticsmentioning
confidence: 98%